Finite Element Analysis of the Pressure Vessels with Various Materials and Thicknesses (International Journal of Scientific Research and Management (IJSRM), 2024)
Pressure vessels are widely used in many areas. Ensuring the safe operation of pressure vessels is particularly important, especially in residential and industrial applications. Errors made during the use of pressure vessels or mistakes during manufacturing and design can lead to significant accidents, resulting in loss of life and property. With the increase in industrialization and energy production, significant advancements have been made in the field of pressure vessels. These vessels are used in various applications, such as heat exchangers in domestic heating systems, and in industrial facilities for the production of steam, superheated oil, and hot water needed for production and separation processes. The advancement of technology and the updating of design and computer aided design programs enable more accurate results in new design and analysis, allowing to produce more reliable and safer materials. To minimize occupational accidents, necessary precautions must be taken in advance. The development of pressure vessels in terms of occupational safety has been ongoing from past to present and is being further enhanced through ongoing studies. In our study, pressure and stress analysis were conducted using the finite element method on ANSYS. Mechanical analyses were repeated for three different thicknesses and three different material types. The purpose of the mechanical analysis was to examine the effect of the thicknesses and different material types on pressure vessels in terms of stress, deformation, and strain.